Characterization of the complete chloroplast genome of Magnolia wilsonii (Magnoliaceae). Issue 2 (3rd July 2019) - Ling, Li-Zhen; Zhang, Shu-Dong
Abstract: The complete chloroplast (cp) genome of Magnolia wilsonii, an endangered and endemic species in China, was first reported in this study. The M. wilsonii cp genome was 157, 434 bp in length, including two inverted repeat (IR) regions of 26, 868 bp, a large single copy (LSC) region of 85, 387 bp, and a small single copy (SSC) region of 18, 311 bp. A total of 113 unique genes, including 79 protein-coding genes, 4 ribosomal RNA genes, and 30 transfer RNA genes, were annotated. The overall GC content was 38.8%. Phylogenetic analysis of 34 representative cp genomes within the genus Magnolia suggests that M. wilsonii was sister to M. sieboldii .